1974
DOI: 10.1128/iai.10.2.335-339.1974
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cell-Mediated Immunity in Experimental African Trypanosomiasis

Abstract: Adult New Zealand white rabbits were experimentally infected with a parasitic African hemoflagellate, Trypanosoma congolense, and were subsequently tested for in vivo and in vitro aspects of cell-mediated immune function. Chronically infected rabbits were sensitized to mycobacterial protein and skin-tested with purified protein derivative; all infected animals demonstrated much milder skin-test responses to antigen than control groups. Similarly, peripheral blood lymphocyte responses in vitro to purified prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Initial evidence for regulation of T‐cell proliferative and cytokine responses by African trypanosomes, as well as evidence for selective down‐regulation of T‐dependent B‐cell responses, led the way for dissection of immunosuppressive events in infection (62–64). Although disparate mechanisms were first proposed to explain suppression of T cells (65,66), it was ultimately clear that ‘suppressor macrophages’ and their products were generated by infection that exhibited a capacity to depress host T‐cell responses (4,6–8,11,12,67,68).…”
Section: Regulation Of T Lymphocyte Responsesmentioning
confidence: 99%
“…Initial evidence for regulation of T‐cell proliferative and cytokine responses by African trypanosomes, as well as evidence for selective down‐regulation of T‐dependent B‐cell responses, led the way for dissection of immunosuppressive events in infection (62–64). Although disparate mechanisms were first proposed to explain suppression of T cells (65,66), it was ultimately clear that ‘suppressor macrophages’ and their products were generated by infection that exhibited a capacity to depress host T‐cell responses (4,6–8,11,12,67,68).…”
Section: Regulation Of T Lymphocyte Responsesmentioning
confidence: 99%
“…1980), which suggests that trypanosomes may enhance antigen-specific lymphocyte functions. On the other hand, the proliferative response to lectins or unrelated antigens is rapidly abrogated (Jayawardena & Waksman 1977, Fierer & Askonas 1982, Mansfield & Wallace 1974, Pearson et al 1978. We found that by day 7 of infection, lymphocytes were producing enhanced amounts of lymphokine upon concanavalin A stimulation.…”
Section: Discussionmentioning
confidence: 57%
“…Cell-mediated immunity such as delayed type hypersensitivity and contact sensitivity reactions which involve immune T-lymphocytes appear to be depressed in chronic (Pearson et al 1978, Yamamoto et al 1985 but not in acute infections (Tizard & Soltys 1971, Freeman et al 1973, Urquhart et al 1973, Murray et al 1974b. To our knowledge, the only study to date on the production of lymphokines directed to macrophages comes from Mansfield & Wallace (1974) who showed that during T. congolense infection lymphocytes fail to secrete migration inhibitory factor.…”
Section: Introductionmentioning
confidence: 99%
“…The depression of the specific IgG response to an injected immunogen associated with a concurrent infection with E. cuniculi is paralleled by observations in other parasitic diseases (7,8,10). A number of mechanisms have been suggested to account for such observations in trypanosomiasis, including depression of By-cell function (16), depression of"helper" T-cell function (14), and macrophage dysfunction or anti- genic competition (20). The elevation ofthe specific IgM response toB.…”
Section: Resultsmentioning
confidence: 90%